IMPACT OF BARIATRIC SURGERY ON GUT MICROBIOTA - Shagazatova Barno Khabibullayevna; Vafoyev Shakhzod Farhod ugli; Sardorova Nozila Otabekovna (Modern American Journals, 2025)
Obesity is associated with gut microbial dysbiosis, reduced microbial diversity and metabolic disturbances. Bariatric surgery (notably Roux-en-Y gastric bypass, sleeve gastrectomy and biliopancreatic diversion) is an effective treatment for morbid obesity and its comorbidities. Increasing evidence suggests that beyond mechanical restriction and malabsorption, bariatric procedures exert profound effects on the gut microbiota, altering microbial composition, metabolic function, and host–microbe interactions. These shifts may contribute to improved insulin sensitivity, inflammation modulation, altered energy harvest, and appetite regulation. However, the temporal dynamics, mechanistic mediators, and long-term stability of microbiota changes remain incompletely understood. This article reviews current knowledge on how different bariatric procedures affect gut microbiota (taxonomic, functional, metabolomic), the plausible mechanistic pathways (bile acids, pH, gut transit, hormonal shifts), and the clinical significance of such microbial modulation for metabolic outcomes.
Keywords: Bariatric surgery, gut microbiota, microbial diversity, metabolic outcomes, bile acids, gut hormones